Recombinant DNA-produced alpha 1-antitrypsin administered by aerosol augments lower respiratory tract antineutrophil elastase defenses in individuals with alpha 1-antitrypsin deficiency. - Hubbard, R C (1989)
Alpha 1-Antitrypsin (alpha 1AT) deficiency is characterized by insufficient amounts of alpha 1AT to protect the lower respiratory tract from neutrophil elastase, resulting in emphysema. Yeast-produced recombinant alpha 1AT (rAAT) has normal antielastase function but is associated with high renal clearance, thus obviating chronic intravenous administration. As an alternative, we evaluated aerosol administration of rAAT to alpha 1AT-deficient individuals. After aerosol administration of single doses of 10-200 mg of rAAT, epithelial lining fluid (ELF) alpha 1AT antineutrophil elastase defenses were augmented in proportion to the dose of rAAT administered. ELF alpha 1AT levels and antineutrophil elastase capacity 4 h after 200 mg rAAT aerosol were increased 40-fold over preaerosol levels, and were fivefold increased over baseline at 24 h after aerosol administration. rAAT was detectable in serum after aerosol, indicating that the lower respiratory tract epithelium may be permeable to rAAT, and that aerosolized rAAT is capable of gaining access to lung interstitium. No adverse clinical effects were noted. These observations demonstrate that aerosol administration of rAAT is safe and results in significant augmentation of lung antineutrophil elastase defenses, suggesting this method is a feasible approach to therapy. Because this approach is clinically unproven, further studies will be necessary to establish the long-term clinical efficacy of aerosol therapy in alpha 1AT deficiency.